SCIENTIFIC APPROACH TO PROBLEMS AND SOLUTIONS IN THE STUDY OF A FOREIGN LANGUAGE - Kurbanova, Muxabbat (Журнал иностранных языков и лингвистики, 2023)
Our article considers the problems of learning a foreign language by scientists and the analysis of what was done on the basis of decisions made at the height of learning a foreign language in the present.